Study of Ti+C combustion synthesis reaction in a controlled declining temperature state - Mahmoodian, R.A.B.; Hassan, M.A.A.C.; Ghadirian, S.B.; Hamdi, M.A. (Taylor and Francis Inc., 2014)
The purpose of this article is to synthesize a Ti-C system under a known cooling rate by applying a secondary hybrid system in the form of semi-reacted titanium carbide. The synthesis reaction is performed in a hot, inert, shielded crucible. The portions of reacting and interacting materials are determined using the Rietveld phase quantification method. The product microstructure is studied, and the nanomechanical properties are measured via a nanoindentation technique. The experimental results revealed that the reaction behavior and mechanical properties of Ti+C elemental powder were initiated at a particular temperature level. At 2610Â°C, the titanium carbide phase formed 14 of the compound composition, with 65 GPa Youngs modulus and 563 MPa hardness. Copyright Â© 2014 Taylor & Francis Group, LLC.